Comparison of ultrasound-guided joint reduction with traditional methods in the emergency center - Eriten, Semih; İzci, Vedat; Menekşe, Serdar (The European Research Journal, 2025)
Objectives: This study aimed to compare and analyze the reliability of ultrasound-guided procedures and traditional methods in the reduction of joint dislocations in the emergency department. Methods: A total of 136 cases were included in the prospective randomized controlled study. The cases were randomized into groups as ultrasound-guided reduction (n=66) and traditional reduction (n=70). The reduction success, time spent for the procedure, complication rates, pain scores and patient satisfaction levels were evaluated. Functional results and osteoarthritis development were also analyzed in long-term follow-up. Chi-square test, Student t-test and Mann-Whitney U test were used in the statistical analysis of the data. Results: The success rate in the ultrasound reduction group (93.9%) was significantly higher than in the conventional reduction group (71.4%) (P